Comparison of pharmacokinetic parameters calculation techniques in studies with animal-point design - V. M. Kosman; M. V. Karlina; M. N. Makarоva; V. G. Makarov (Фармакокинетика и Фармакодинамика, 2023)
In pharmacokinetics (PK) studies of medicinal products with small laboratory animals models, primarily rodents, the design of the animal-point experiment is often used, involves the selection of biological material after euthanasia of the animal. The question of experimental data processing and the PK parameters calculation method in a situation where all concentration values  are obtained from diﬀerent individuals is relevant.Purpose of the study. Comparison of pharmacokinetic parameters calculation methods in studies with the animal-point design.Materials and methods. For a number of previously conducted studies with male outbred rats test systems, a retrospective data analysis was performed and PK parameters were calculated in three diﬀerent ways: from the average concentration values at each time point (method 1): from data obtained for animals with the same sequence numbers in subgroups corresponding to time points (method 2); using resempling based on modeling of individual PK proﬁles (method 3). Pharmacokinetic parameters (maximum concentration — Cmax, time to reach maximum concentration — Tmax, area under the curve "concentration-time" — AUC0-t, average time to stay in the body — MRT, half-life — T1/2) were calculated by non-compartment method of statistical moments using the validated PKSolver application for Microsoft Oﬃce Excel.Results. The comparison of the obtained results did not reveal any patterns and preferences for the use of a particular method of calculating PK parameters depending on the studied drugs, route and administration way. For all evaluated PK parameters (Cmax, Tmax, AUC0-t, MRT, T1/2), similar values and/or intervals were obtained, which indicated the correctness of all considered calculation methods.Conclusion. Based on advantages and disadvantages of the calculation methods comparison it is shown that it is optimal to use method 2, which is a special case of reception (method 3) with a minimum number of replications. It is important to emphasis the method of PK parameters calculation when describing the methodology of studies to improve their quality.